The Improved Key Exchange Protocol Based on Public Key Certificates - Cuijie Zhao; Guozhen Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
We propose mutual authentication and session key exchange protocols based on certificates for the Internet of Things. We also propose an improved version for the conventional certificate-based systems. Our protocol is efficient, it requires fewer messages and only one session key. It gives use a new method to deal with such as preventing tampering and preventing interference security problems. In designing the security protocol proposed here, the low computational power of the wireless sensors nodes and the low bandwidth of the wireless networks are considered. It is good as low computational complexity and cannot be forged. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4775